Сучасний підхід до виокремлення функцій органів Національної поліції України у сфері забезпечення державної інформаційної політики - Негодченко, В. О.; Nehodchenko, V. O. (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 176–188, 2016)
Визначено особливості участі Національної поліції України у формуванні та реалізації державної інформаційної політики, подано перелік і розкрито зміст та відповідних функцій її органів та підрозділів. Характеризовано специфіку забезпечення державної інформаційної політики в контексті реалізації кожної функції Національної поліції як центрального органу виконавчої влади загалом і на прикладі її окремих структурних складових. Наголошено на необхідності законодавчого закріплення (в законі України «Про Національну поліцію») основних функцій Національної поліції та чіткого окреслення заходів, які мають здійснюватися з метою їх належної реалізації за всіма напрямами діяльності органів і підрозділів Національної поліції, в тому числі в інформаційній сфері. Звернуто увагу на пріоритетність ухвалення окремого нормативно-правового акта, в якому повинні знайти своє відображення питання реалізації органами та підрозділами Національної поліції заходів щодо протидії кіберзлочинності.

The author has determined the features of participation of the National Police of Ukraine in the formation and implementation of the state information policy; has provided the list and revealed the content of the functions of its agencies and divisions. The separation of functions of the National Police into general, special and auxiliary has been grounded. It has been emphasized that the provision of information policy of the state by the police agencies and divisions belongs to all functions of this body of executive power. This is due to the fact that the National Police agencies within the implementation of special functions take measures to combat crime, ensure public safety and order, protection of the rights and freedoms, public interests from unlawful encroachments, etc. It has been established that these activities are carried out in all spheres of public life, including information one. The author has characterized specifics of providing the state information policy in the context of realization of each function of the National Police as the central executive body in general and by the example of individual structural components. It has been emphasized on the necessity of legislative consolidation (within the Law of Ukraine “On the National Police”) of the main functions of the National Police and the clear delineation of the range of measures to be taken with the aim of their proper implementation in all directions of the activities of the agencies and divisions of the National Police, including with the information sphere. It has been also indicated that in the context of mainstreaming the issue of cybersecurity, the adoption of a separate regulatory act acquires the priority. This act should reflected he issues of implementing the measures on combating cybercrime by the National Police agencies and divisions.

Определены особенности участия Национальной полиции Украины в формировании и реализации государственной информационной политики, подан перечень и раскрыто содержание соответствующих функций её органов и подразделений. Охарактеризована специфика обеспечения государственной информационной политики в контексте реализации каждой функции Национальной полиции как центрального органа исполнительной власти вообще и на примере её отдельных структурных составляющих. Отмечена необходимость законодательного закрепления (в законе Украины «О Национальной полиции») основных функций Национальной полиции и чёткого определения круга мероприятий, которые должны осуществляться с целью их надлежащей реализации по всем направлениям деятельности органов и подразделений Национальной полиции, в том числе в информационной сфере. Обращено внимание на приоритетность принятия отдельного нормативно-правового акта, в котором должны найти своё отражение вопросы реализации органами и подразделениями Национальной полиции мер по противодействию киберпреступности.
The modern approach to the separation of the functions of the National Police agencies of Ukraine in the sphere of ensuring the state information policy
Современный подход к выделению функций органов Национальной полиции Украины в сфере обеспечения государственной информационной политики
Негодченко, В. О. Сучасний підхід до виокремлення функцій органів Національної поліції України у сфері забезпечення державної інформаційної політики / В. О. Негодченко // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 176–188.
Негодченко В. О. "Сучасний підхід до виокремлення функцій органів Національної поліції України у сфері забезпечення державної інформаційної політики." Вісник Харківського національного університету внутрішніх справ 4 (2016): 176-188.
Nehodchenko, V.O. (2016), “The modern approach to the separation of the functions of the National Police agencies of Ukraine in the sphere of ensuring the state information policy” [Suchasnyi pidkhid do vyokremlennia funktsii orhaniv Natsionalnoi politsii Ukrainy u sferi zabezpechennia derzhavnoi informatsiinoi polityky], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 176–188.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; державна інформаційна політика; функції; інформаційна сфера; кібербезпека; поліція; National police of Ukraine; state information policy; functions; information scope; cyber security; Национальная полиция Украины; государственная информационная политика; функции; информационная сфера; кибербезопасность; полиция; police